Consideration of Liver Function test with Erythropoietin Hormone Levels in Iraqi Patients Diagnosed with Lymphoid and Myeloid Leukemia - Rezaieg, Nour Sh (Iraqi Journal of Cancer and Medical Genetics, 2018)
The study was carried out to measure the erythropoietin hormone level and a number of the hematological variables (red blood cells, platelets, monocytes and lymphocytes) and biochemical variables (erythropoietin, alkaline phosphatase, alanine transaminase and aspartate transaminase) for two types of leukemia (lymphoid leukemia and myeloid leukemia). Enzyme Linked Immune Sorbent Assay (ELISA) was used to detect level of erythropoietin in patients with lymphoid and myeloid, leukemia and control group , liver enzymes activity were measured including alkaline phosphatase (ALP) alanine transaminase (ALT) and aspartate transaminase (AST). Also estimated some hematological variables were estimated: red blood cells, platelets, lymphocytes and monocytes, as well as, ABO blood groups in all studied groups. The statistical analysis showed significant (P< 0.05) increase in the level of erythropoietin, liver enzymes, lymphocytes and monocytes number in patients with lymphoid and myeloid leukemia when compared with the control group. While, there was a decrease (P< 0.05) in red blood cells count and platelets count in the patients groups compared with the healthy group. Also, the results from statistical analysis revealed that there was a strong correlation between ABO blood groups and leukemia.